The simulation models for human pedestrian movement of a departure process in an airport - Noor Akma, Abu Bakar; Allegra, Mario; Anis Izzati, Ab Fauzan; M., Fakhreldin; Mazlina, Abdul Majid (2018)
The emergence of simulating human movement and behaviour rose in order to imitate and replace human interference with this complex demeanour. It is so diverse and uncontrollable to the extent it is almost impossible to undergo exhaustive experiments. Hence, simulating this model is crucial. Especially in designing a public area where human density is too much concentration and the need for properly planned traffic or human movement is very much needed. For that, simulations and modelling are always the best options for investigating human behaviour. In this research work, the aim is to investigate how effective and to what extent the Agent-Based Simulation (ABS), Discrete Event Simulation (DES) and hybrid of both give benefits to the society adequately. Its expected results will be an improved and better version of human pedestrian movement in the airport of the departure process simulation model.